Barriers and motivators to participation and retention in HIV/HCV cohort studies among people who inject drugs: a community consultation in Iran - Ali Mirzazadeh; Samira Hosseini-Hooshyar; Armita Shahesmaeili; Ali Bahramnejad; Adibeh Barshan; Ghazal Mousavian; Esmail Najafi; Hamid Sharifi; Ali-Akbar Haghdoost; Alya Briceno; Willi McFarland; Kimberly Page (BMC, 2020)
Abstract Background The lack of robust estimates of HIV/HCV incidence among people who inject drugs (PWID) in Iran calls for well-designed prospective cohort studies. Successful recruitment and follow-up of PWID in cohort studies may require formative assessment of barriers PWID are faced with in participation and retention in cohort studies and factors they think may facilitate their engagement in such studies. Using a focus group discussion (FGD) format, we conducted a consultation with PWID in southeast Iran to recognize those barriers and motivators. Methods Using targeted sampling and through snowball referrals, we recruited PWID (aged≥18, injected in last 6 months) from community-based drop-in centers (DICs), homeless shelters, and through outreach efforts to participate in four FGDs (one women-only). Socio-demographic characteristics, injection behaviors and self-reported HCV/HIV testing and diagnosis history were obtained. Then, a semi-structured FGD guide was applied to explore barriers and motivators to participation and retention in cohort studies among study participants. All FGD sessions were recorded and transcribed verbatim, removing any identifying information. The content of FGDs were analyzed by thematic analysis using an inductive approach. Results In total, 30 individuals (10 women) participated in the study. The median age of participants was 35 (IQR 31-40), with majority (73.3%) reporting injecting drug use within the last month. Only 40.0% reported ever being tested for HCV whereas a larger proportion (63.4%) reported ever being tested for HIV. While the majority were willing to participate in cohort studies, breach of confidentiality, fear of positive test results, perceived required commitment, and marginalization were reported as barriers to participation and retention in such studies. Monetary incentive, the thought of a better life, protection from police interventions and trust between health workers and PWID were addressed as motivators of engagement in cohort studies among PWID. Conclusions Strategies to enhance data security and reduce stigma associated with injecting drug use along with involving peer workers in research, providing pre and post-test counselling and education and addressing the needs of more marginalized groups potentially through integrated healthcare programs and housing support are among few approaches that may help address barriers and strengthen the motivators for successful cohort studies among this population.